Study of Pharynx and Laryngeal Clinical Characteristicsin Gastroesophageal Reflux Patient (Latakia University Journal -Medical Sciences Series, 2023)
Gastroesophageal reflux is the reflux of stomach contents (Acid-Liquid-Gases) towards the esophageal tract, this regurgitation causes symptoms within the digestive system witch known as typical gastroesophageal reflux, or it may causes symptoms outside the digestive system within the upper respiratory tract, when it is known as  Atypical gastroesophageal reflux or laryngopharyngeal reflux (LPR), the symptoms of LPR are very similar to several diseases of the upper respiratory tract.The aim of this study is to find out the most common symptoms and clinical signs caused by gastroesophageal reflux in the pharynx and larynx, to establish  early diagnosis, to identify possible treatment methods, and to study the improvement of these symptoms and signs after applying treatment